Additions to Earlier Inventories of the Sacred Groves in Satara District, Maharashtra - Ghate, Vinaya; Kore, Priti; Adkar, Ramkrishna (Indian Forester, 2018)
During field studies for our project on reassessment of the sacred groves from Satara district, Maharashtra we came across number of unreported sacred groves from the study area. As many as 65 new sacred groves have been added to the previous inventories through forest records, local inhabitants and search through G-map. These newly reported locations have been verified as the sacred groves using G-map as well as visiting the sites. Present paper deals with new additions to the earlier inventories focusing on name of sacred groves, nearest village with taluka and associated deity. The sacred groves being precious as hot spots of biodiversity, this enriched inventory is vital for decision making on conservation strategies.